Thermal stability of Al-Cu-Mg-Ag hub forgings - LEI Yue; ZANG Jinxin; XING Qingyuan; HAO Min; CHEN Gaohong (Journal of Aeronautical Materials, 2024)
The room temperature tensile properties and elevated temperature tensile properties of peak aged Al-Cu-Mg-Ag hub forgings after different heat exposure temperatures and heat exposure time were tested，and the thermal stabilities of the forgings at different temperatures were compared and analyzed. The results show that Al-Cu-Mg-Ag forgings exhibit good thermal stability. After exposure at 150 ℃ for 1 to 100 h，there were no significant changes in room temperature tensile properties and elevated temperature tensile properties. Short time heat exposure at 150-200 ℃ for 1 h does not reduce the overall performance，but the strength of Al-Cu-Mg-Ag forgings decreases with the increase of heat exposure temperature and the extension of heat exposure time. After 100 h of exposure at 200 ℃ and 250 ℃，the room temperature yield strength remains 61.1% and 37.2 %，and the room temperature tensile strength remains 77.8% and 60.8%，the elevated temperature yield strength remains 61.6% and 42.8%，and the elevated temperature tensile strength remains 67.5% and 47.6%，respectively. The main precipitates of Al-Cu-Mg-Ag forgings are Ω phase and θ′ phase. Under the experimental conditions of Kt=1 and R=0.1，the room temperature fatigue limit after 200 ℃/10 h heat exposure is 278 MPa，which is 10.6% lower than the fatigue limit of 311 MPa before heat exposure.